Expectations and disappointments on the part of institutions in the process of reception and integration of refugees in Portugal - Magano, Olga (2023)
Portugal joined the European movement to welcome refugees in 2015, and there was an unprecedented phenomenon of civil society mobilization to provide shelter to refugees, overlapping at times the State. The model adopted for hosting refugees was related to the involvement of civil society, which meant that the relocation program assumed two structuring characteristics: the geographical dispersion of refugees throughout the country and the institutional diversity of the structures that carried out their placement. To know the practices developed by the host institutions and the circumstances of the interaction between their staff and refugees allows us to understand the role of local agency aimed at the reception of refugees and its impacts. Attitudes and feelings of disillusionment and disappointment can clash with the expectations of welcoming initiatives, which are often based on a constructed image of refugees as grateful, innocent victims and deserving of help. The aim of this article focuses on the practices and perceptions of representatives of local institutions regarding their relocation experiences. Thus, results obtained on the relocation process from the point of view of the institutions and on opportunities and challenges faced for the integration of refugees relocated in Portugal, as well as feelings, expectations and disappointments, are presented.